Dicrostonyx rubricatus - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Dicrostonyx rubricatus (Richardson, 1889). The Zool. of Captain Beechey's Voy., p. 7. TYPE LOCALITY: U.S.A., Alaska, Bering Strait. DISTRIBUTION: N. Alaska (U.S.A.). COMMENT: The diploid numbers are 33 and 42 for males, 32 and 34 for females; the fundamental number is 55; formerly included in torquatus; see Rausch, 1977, in Sokolov, ed., [Adv. Mod. Theriol.], Acad. Sci. U.S. S.R., Nauka, Moscow, pp. 162- 177; or groenlandicus; see Hall, 1981:836. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 4), pp. 477-504 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 483, DOI: 10.5281/zenodo.7353034